The Effect of Using 3D Printed Insole and Semi-Rigid Insole on Spatiotemporal Parameters in Students with Flexible Flat Foot Deformity - Anatasia, Suci; Karma, Agusni; Yunihanawati, Rizan; Yulianto, Bayu Sholeh (Poltekkes Kemenkes Jakarta I, 2024)
Background: The most common foot deformity in the community is the flexible flat foot where the MLA condition becomes flat. Flat foot deformity results in decreased spatiotemporal gait parameters and requires an orthosis like an insole. Usually, flat feet are given a semi-rigid insole, but there is an alternative to the modeling and fabrication process of the insole, called the 3D printing method. Aims: To analyze the effect of 3D printed insole and semi-rigid insole on spatiotemporal gait parameters (walking speed, cadence, and step length). Methods: Using a quantitative analysis with cross sectional design to observe the improvement on spatiotemporal gait parameters. Five flexible flatfeet participants were recruited and asked to walk about 10-meter with 3D printed insoles. Results: There was an increase in walking speed after using 3D printed insoles on spatiotemporal parameters (speed, cadence, and stride length). Conclusion: The use of a 3d printed insole can help improve walking speed in participants with flexible flat foot deformity.